(untitled) (Journal of Agriculture & Rural Development, 2010)
A field experiment on okra taking the variety BARI Dharos-1 with four nitrogen levels (0, 75, 125 and 175 kg/ha) and six levels of green fruit picking (no green fruit picking, first two, first four, first six, first eight and first ten green fruit picking) was conducted at the Agricultural Research Station, Raikhali, Rangamati Hill District to find out the optimum N level and suitable number of green fruit picking during the summer seasons of 2005 and 2006 for the highest economic benefit. The plants were grown for both vegetable and seed production. Growth parameters, green fruit as well as dry fruit characters, seed yield attributes were significantly affected by different levels of N and green fruit picking. Nitrogen levels and green fruit picking increased number of dry fruits per plant, number of seeds per fruit, weight of seeds per fruit and seed yield. Application of N @ 125 kg/ha gave the highest fruit and seed yield of okra followed by 175 kg N/ha. These two N levels also produced maximum 100-seed weight, percentage of germination and seed vigour. The treatment of picking of 10 green fruits produced the highest green fruit yield/ha. But picking of first 4 green fruits produced maximum seed yield, which was statistically at par with those of 2 and 6 green fruits picking. First 4 green fruit picking gave the highest seed vigour whereas first 6 green fruit pickings produced maximum 100-seed weight. Picking of first 4 green fruits accompanied with 175 kg N/ha gave the highest seed yield of 2.86 t/ha, which was closely followed by picking of first 2 or 6 green fruits with 125 kg as well as 175 kg N/ha. Picking of first 2 or 4 green fruits in combination with 125 kg N/ha also gave the similar seed yield. The combination of 125 kg N/ha and first 6 green fruit picking gave the highest gross income (Tk.193.56/ha), net return (Tk.126.35/ha) and maximum BCR of 2.88. Key words: Nitrogen; picking; okra; fruit and seed yield; profitability. DOI: 10.3329/jard.v7i1.4428 J Agric Rural Dev 7(1&2), 99-106, June 2009